Physical chemistry for the life sciences - Atkins, P. W. (Peter William) 1940-; De Paula, Julio (New York W.H. Freeman and Co., 2011)
Peter Atkins and Julio de Paula offer a fully integrated approach to the study of physical chemistry and biology.
Includes bibliographical references and indexes.
Keywords: Physical biochemistry; Chemistry, Physical and theoretical; Life sciences